Chemical Constituents from the Fruits of Lycium chinense and Antioxidant Activity - Chung, Ill-Min; Praveen, Nagella; Kim, Sun-Jin; Ahmad, Ateeque (Asian Journal of Chemistry, 2011)
Three compounds glucopyranosyl-1-octadec-9',12',15'-trienoyl-6-octadec-9'',12''-dienoate (1), glyceryl-1-octadec-9',12',15'-trienoyl-2-octadec-9'',12''-dienoyl-3-hexadecanoate (2), glyceryl- 1-octadec-9',12',15'-trienoyl-2-octadec-9''-enoyl-3-eicosanoate (3), have been isolated from the ethyl acetate extract of fruits of Lycium chinense. Their structures have been elucidated with the help of 600 MHz NMR using 1D spectral method viz.: 1H and 13C, aided by FAB MS and IR spectroscopy. The compounds 1-3 are reported for the first time in the fruits of L. chinense and data also compared with similar compounds. The compounds from the ethyl acetate extract of the Lycium fruits were investigated for scavenging of the diphenylpicrylhydrazyl (DPPH) radical activity and the reducing power and the results demonstrate that the compound 1 has potential as a natural antioxidant whereas the compounds 2 and 3 exhibited low antioxidant activity.